Advances in Transition Metal Seleno‐ and Tellurocarbonyl Chemistry. Issue 56 (7th September 2020) - Frogley, Benjamin J.; Hill, Anthony F.; Watson, Lachlan J.
Abstract: In contrast to the ubiquity of transition‐metal carbonyl, and (to a lesser extent) thiocarbonyl complexes, transition‐metal complexes of carbon monoselenide L n MCSe and monotelluride L n MCTe remain scarce. The last few years, however, have seen notable steps towards expanding this chemistry, specifically with regards to new systematic studies on homologous sets of chalcocarbonyl complexes L n MCE (E=O, S, Se, Te), the first reports of new bi‐ and polynuclear CSe and CTe bridging complexes and a confluence with metal carbido chemistry. Herein the properties, syntheses and reactions of these rare but fundamentally intriguing compounds are discussed. Abstract : Distinguished d‐complexes : Recent developments in the chemistry of transition metal selenocarbonyl (L n MCSe) and tellurocarbonyl (L n MCTe) complexes have provided new insights into how the heavier chalcocarbonyls distinguish themselves from the more commonly encountered carbonyl (CO) and thiocarbonyl (CS) ligands.